Mapping factors associated with deaths in immigration detention in the United States, 2011-2018: A thematic analysis - Parveen Parmar; Madeline Ross; Sophie Terp; Naomi Kearl; Briah Fischer; Molly Grassini; Sameer Ahmed; Niels Frenzen; Elizabeth Burner (Elsevier, 2021)
Background: Climate change, poverty, and violence increasingly drive migration to the United States. United States Immigration and Customs Enforcement (ICE) detain some individuals while awaiting determination of immigration status or potential deportation. Over the last two decades, more than 200 individuals died in ICE detention. In this study, we aim to identify systemic issues related to deaths of individuals in ICE detention to potentially mitigate further harm. Methods: The ICE Office of Detention Oversight conducts investigations after each death in detention, producing a report called a "Detainee Death Review". To identify systemic issues in these deaths, we used thematic analysis to review 55 Detainee Death Reviews available between 2011 and 2018. Findings: We identified 3 major themes of pervasive issues-Detainee Not Patient, System Over Patient, and Grossly Substandard Care- and 11 subthemes. Subthemes of culture of shortcuts, delays in care, and poor care delivered were present in the vast majority of cases. Subthemes bias and discrimination, language injustice, falsification of and inconsistencies between records and reports, willful indifference, security over health, communication breakdown, inadequate resources, failure of protective mechanisms, missing/ignoring red flags, and failure of emergency response were also prominent. Interpretation: This study identified underlying systems issues within the medical care provided in ICE detention. While there are issues with language services, discrimination, and inadequate response to medical emergencies, the greatest issue is the lack of independent, external review. Greater transparency is required, so that adherence to basic standards of care for individuals in ICE detention can be better evaluated. Funding: Haas Jr. Fund and the University of Southern California's Equity Research Institute.